1992
DOI: 10.5144/0256-4947.1992.456
|View full text |Cite
|
Sign up to set email alerts
|

CT Scan Findings of Occult Sinus Pathology in Asymptomatic Individuals

Abstract: One hundred-fourteen computed tomographic (CT) scans of the skull region were revised for occult sinus pathology in asymptomatic individuals. The scans were conducted to investigate other skull regions. None of the patients had nasal or sinus symptoms. Twenty-nine percent of the ethmoid sinuses had occult pathology mostly in the form of thickened mucous membrane. Occult pathology occurred in 14% of maxillary sinuses, 4.8% of the frontal sinuses, and 4.6% of the sphenoid sinuses. As ethmoids carry a high incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Nine of the studies excluded from the meta‐analysis due to incomplete data found a combined 12.8% prevalence of some degree of maxillary sinus mucosal thickening. However, they did not describe the criteria used to classify pathological thickening of the maxillary sinus mucosa 19,24,35–41 . Two additional studies reported maxillary thickening >3 mm combined with additional findings, but individual data could not be extracted to be included in the meta‐analyses performed here 20 , 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the studies excluded from the meta‐analysis due to incomplete data found a combined 12.8% prevalence of some degree of maxillary sinus mucosal thickening. However, they did not describe the criteria used to classify pathological thickening of the maxillary sinus mucosa 19,24,35–41 . Two additional studies reported maxillary thickening >3 mm combined with additional findings, but individual data could not be extracted to be included in the meta‐analyses performed here 20 , 25 .…”
Section: Resultsmentioning
confidence: 99%
“…However, they did not describe the criteria used to classify pathological thickening of the maxillary sinus mucosa. 19,24,[35][36][37][38][39][40][41] Two additional studies reported maxillary thickening .3 mm combined with additional findings, but individual data could not be extracted to be included in the meta-analyses performed here. 20,25 Finally, 1 study reported a 37.5% prevalence of maxillary sinus mucosal thickening 1 mm.…”
Section: Maxillary Sinus Mucosal Thickening 2 MMmentioning
confidence: 99%